The role of sentinel lymph nodes in breast cancer. The current state of the problem. - Aliya Yermagambetova; Abay Makishev; Khalel Imanbayev (National Scientific Medical Center, 2017)
Sentinel lymph nodes (SLN) biopsy is currently the standard procedure for axillary staging in patients with invasive breast cancer and clinically negative lymph nodes (cN0). Historically, all patients with a positive sentinel lymph node (SLN) undergo classical axillary lymph node dissection (ALND). A randomized clinical trial in patients with breast cancer with clinical T1-2N0M0, with positive SLN afterwards undergo classical ALND showed that women diagnosed with T1-T2 and cN0 who underwent breast-conserving surgery and radiation therapy can safely avoid ALND. The main goal of SLN examination should be the detection of all macrometastases (> 2 mm). The role and timing of SLN in patients who received neoadjuvant polychemotherapy is still controversial and continues being studied in clinical trials.